Upaya Menegakkan Budaya Etika Akademik Dalam Perguruan Tinggi - Nasywa Nur Zhafira; Fitri Nabila; Siti Nurul Latifah; Lailatul Husna Br. Regar; Nabilla Azzahra; Rizki Akmalia (Realisasi : Ilmu Pendidikan, Seni Rupa dan Desain, 2024)
Academic ethics are ethics that must be used as a reference for the academic community to behave during the learning process. Many violations that occur in the educational environment are in the form of cheating caused by internal and external factors. The phenomenon of academic cheating is increasing and has taken root in the world of education, especially students. There are so many lies that occur in the world of education which result in a student's ethics not being created properly, therefore this article was created to increase insight into what efforts can be made to uphold a culture of academic ethics in higher education.